Total synthesis of rhizopodin - Dieckmann, Michael; Kretschmer, Manuel; Li, Pengfei; Rudolph, Sven (Angewandte Chemie. International edition, 2012)
Symmetry helps: The total synthesis of the potent actin-targeting C2-symmetric myxobacterial macrolide rhizopodin (see scheme) is accomplished by the convergent assembly of three building blocks of similar complexity, a concise macrocyclization strategy, and a late-stage introduction of the labile side chains.
Gesehen am 18.12.2018